KOZMOLOGICKÉ DIMENZIE PRAVDY A KLAMSTVA V ĽUDOVÝCH ROZPRÁVKACH - Ľubomír Gábor (Conversatoria Litteraria, 2019)
The order analyses west Slavic folk tales about Jesus Christ and St. Peterʹ s wandering on the Earth, which does not correspond with the Holy Bible. The paper attempts to prove, that there may be found some functional similarities between couples Jesus Christ – St. Peter and Mitra – Varuna as representants of the Indo-European mythological tradition. They had represented the cosmologi-cal connection of antagonistic elements – day and night, life and death, truth and lie etc. Jesus Christ and St. Peter as figures – functions in the folk tales should symbolize difficult relationships between the truth and lie.